Comparative Evaluation of Pattern of Anterior Loop of Mandibular Canal in Dentulous and Edentulous Patients Using Cone Beam Computed Tomography: A Cross-Sectional Study - Kalyani Khairnar; Chetan Bhadage; Ajay Bhoosreddy; Madhura Barve (Journal of Indian Academy of Oral Medicine and Radiology)
Background: Previous literature has discussed the prevalence of various patterns of anterior loops in male and female populations. We rarely encounter studies examining the patterns of anterior loops in dentulous and edentulous patients. Objective: To determine whether the pattern of the anterior loop of mandibular canal changes due to atrophic changes in edentulous compared to dentulous patients. Methods: 100 cone beam computed tomography scans of 50 dentulous and 50 edentulous patients were included. The mandibular canal was traced bilaterally after converting the data into DICOM format. The anterior loop of the mandibular nerve was classified into three types (I, II, and III) according to the system proposed by Solar et al. (1994). Results: The difference in the pattern of the anterior loop in dentulous and edentulous patients was statistically insignificant. No statistically significant difference was observed in the patterns of the anterior loop between genders. Conclusion: The Type II pattern was most common in dentulous and edentulous groups, with no significant statistical differences in the distribution of patterns. Similarly, Type II was most common in both genders, but the difference was not statistically significant.